2019
DOI: 10.3390/catal9070608
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic and Antibacterial Performance of ZnO Nanoparticles Prepared by an Efficient Thermolysis Method

Abstract: ZnO nanoparticles (ZnO-NPs) were synthesized by a straightforward modified thermal method using only one chemical: zinc acetate dihydrate. The process is environmentally safer than other methods because it does not involve other chemicals or a catalyst, acid, or base source. X-ray diffraction analysis indicated that the ZnO-NPs crystallize in the hexagonal wurtzite structure. The UV–vis absorption spectra revealed a marked redshift, which is critical for enhanced photocatalytic activity. We used methylene blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Khatami et al 51 reported that the biosynthesized ZnO NPs with a size of 2.8 nm demonstrated higher inhibitory activity with lower MIC value at 2.0 µg/mL against S. aureus and E. coli. Also, Abu Hanif et al 52 demonstrated that the synthesized ZnO NPs inhibits the growth of E. coli at a comparatively lower concentration of 50 µg/mL, and they suggested that the antibacterial activity of ZnO NPs is size-dependent. Contradictory to our findings, the biosynthesized ZnO NPs produced in this present study were significant compared to other studies, which resulted in bigger values for MIC and MBC.…”
Section: Resultsmentioning
confidence: 99%
“…Khatami et al 51 reported that the biosynthesized ZnO NPs with a size of 2.8 nm demonstrated higher inhibitory activity with lower MIC value at 2.0 µg/mL against S. aureus and E. coli. Also, Abu Hanif et al 52 demonstrated that the synthesized ZnO NPs inhibits the growth of E. coli at a comparatively lower concentration of 50 µg/mL, and they suggested that the antibacterial activity of ZnO NPs is size-dependent. Contradictory to our findings, the biosynthesized ZnO NPs produced in this present study were significant compared to other studies, which resulted in bigger values for MIC and MBC.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results are consistent with this relationship. Large pores of a catalyst promote the adsorption of organic molecules on its surface during photodegradation, thus increasing its photocatalytic activity 21 . The surface area and pore size values are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Those nanostructures generally grow either along the <0001> or <1010> plane directions [186]. The ratio between the Zn vapor pressure and oxygen pressure, or the Zn/O flux ratio must be carefully monitored for attaining the desired ZnO nanostructures [187] [188].…”
Section: Vapor Phase Routementioning
confidence: 99%